Residual Cochlear Function in Adults and Children Receiving Cochlear Implants: Correlations With Speech Perception Outcomes. Issue 3 (May 2019) - Fontenot, Tatyana Elizabeth; Giardina, Christopher Kenneth; Dillon, Megan T.; Rooth, Meredith A.; Teagle, Holly F.; Park, Lisa R.; Brown, Kevin David; Adunka, Oliver F.; Buchman, Craig A.; Pillsbury, Harold C.; Fitzpatrick, Douglas C.
Abstract : Objectives: Variability in speech perception outcomes with cochlear implants remains largely unexplained. Recently, electrocochleography, or measurements of cochlear potentials in response to sound, has been used to assess residual cochlear function at the time of implantation. Our objective was to characterize the potentials recorded preimplantation in subjects of all ages, and evaluate the relationship between the responses, including a subjective estimate of neural activity, and speech perception outcomes. Design: Electrocochleography was recorded in a prospective cohort of 284 candidates for cochlear implant at University of North Carolina (10 months to 88 years of ages). Measurement of residual cochlear function called the "total response" (TR), which is the sum of magnitudes of spectral components in response to tones of different stimulus frequencies, was obtained for each subject. The TR was then related to results on age-appropriate monosyllabic word score tests presented in quiet. In addition to the TR, the electrocochleography results were also assessed for neural activity in the forms of the compound action potential and auditory nerve neurophonic. Results: The TR magnitude ranged from a barely detectable response of about 0.02 µV to more than 100 µV. In adults (18 to 79 years old), the TR accounted for 46% of variability in speech perception outcome by linear regression ( r 2 = 0.46; p < 0.001). In children between 6 and 17 years old, the variability accounted for was 36% ( p < 0.001). In younger children, the TR accounted for less of the variability, 15% ( p = 0.012). Subjects over 80 years old tended to perform worse for a given TR than younger adults at the 6-month testing interval. The subjectively assessed neural activity did not increase the information compared with the TR alone, which is primarily composed of the cochlear microphonic produced by hair cells. Conclusions: The status of the auditory periphery, particularly of hair cells rather than neural activity, accounts for a large fraction of variability in speech perception outcomes in adults and older children. In younger children, the relationship is weaker, and the elderly differ from other adults. This simple measurement can be applied with high throughput so that peripheral status can be assessed to help manage patient expectations, create individually-tailored treatment plans, and identify subjects performing below expectations based on residual cochlear function.